Economic Analysis and Recommendation of Mobile Virtual Operation Market in China - Haidong Lei; Luona Song; Tingjie Lv; Xia Chen (International Telecommunications Society (ITS), 2017)
With the continuous development and iteration of telecommunication technology, the users' requirements of the quality and service have increased dogmatically. In order to meet the diverse and personalized consumer demands, virtual network operators came into being. In 2013, China officially launched mobile wholesale business pilot which symbolized the arrival of virtual operation in China market. This paper explores the economic effect of China virtual operation from the perspective of consumer surplus and social welfare according to the data of data service from three years after the introduction of virtual operation. The results show that, after introducing virtual operators into China market, consumer surplus and social welfare have both enhanced. Moreover, comparing with the wholesale mode, simple virtual operation mode could provide greater consumer surplus and social welfare. At the same time, MVNO will get more profits. In the early stage, MVNO is in a weak position, but the policy of simple virtual operation mode reflects strong government support. Finally, this paper puts forward some recommendations based on the result of the mathematical model and China's national conditions.
Keywords: 330; Virtual Operation; Mobile Wholesale; Consumer Surplus; Social Welfare